Penerapan Pendekatan Persuasif Guru BK untuk Mengubah Persepsi Siswa Terhadap Ruang BK - Atalya Bernike Br. Barus; Inri Dwi Rianti Manik; Jeanette Abigael Noventa Ujung; Muhammad Reyhan Hersya (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to analyze the implementation of persuasive approaches used by Guidance and Counseling (BK) teachers in changing students’ perceptions toward the counseling room at SMP 35 Medan. This research employed a descriptive qualitative method involving 31 students of class VIII-4 as respondents. Data were collected through interviews, observations, and documentation. The results showed that most students still had negative perceptions of the counseling room, with 22 students or approximately 71% expressing negative views, while 9 students or around 29% had positive perceptions. These negative perceptions arose because the counseling room was often viewed as a place of punishment, a room for problematic students, and a frightening place. However, the persuasive approaches applied by BK teachers through friendly communication, openness, listening to students’ concerns, and building closer relationships were able to change some students’ perceptions into more positive ones. Students felt more comfortable, appreciated, and no longer afraid to visit the counseling room. Therefore, persuasive approaches play an important role in creating positive relationships between BK teachers and students so that counseling services can be better accepted in schools.